2015
DOI: 10.1088/0004-637x/814/2/126
|View full text |Cite
|
Sign up to set email alerts
|

Critical Decay Index at the Onset of Solar Eruptions

Abstract: Magnetic flux ropes are topological structures consisting of twisted magnetic field lines that globally wrap around an axis. The torus instability model predicts that a magnetic flux rope of major radius R undergoes an eruption when its axis reaches a location where the decay index −d(ln B ex )/d(ln R) of the ambient magnetic field B ex is larger than a critical value. In the current-wire model, the critical value depends on the thickness and time-evolution of the current channel. We use magneto-hydrodynamic (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
148
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 40 publications
10
148
0
Order By: Relevance
“…This is the goal of an ongoing study (Zuccarello et al, in prep. ) that focuses on the analysis of the helicity content of the parametric simulations of Zuccarello et al (2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the goal of an ongoing study (Zuccarello et al, in prep. ) that focuses on the analysis of the helicity content of the parametric simulations of Zuccarello et al (2015).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is however interesting to note that H j corresponds to a description of the current part of the field while the |H V |, which is dominated by 2H pj , includes the relative properties of the current-carrying field in relation to its surrounding field. In the framework of the torus instability (Kliem & Török 2006;Démoulin & Aulanier 2010;Zuccarello et al 2015), the criterion of instability is also related to the relative properties of the current-carrying structure with regards to its surrounding confining field. Here we speculate that the ratio |H j |/|H V | may somehow be related to the instability criterion of the torus instability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The derivation of the torus instability criteria based on previous analytical studies took into account perturbations of a static configuration. Thus, a more accurate estimate of the torus index in our simulations would be to let the envelope field relax at each time step and then calculate n. This can only be done if the driver of the system could be stopped, letting the overall magnetic flux system reach an equilibrium (e.g., Zuccarello et al 2015). However, in our dynamical simulations, there is a certain amount of available magnetic flux, which can emerge into the photosphere and above.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For thick channels, the critical index for circular and straight channels does not vary much-it takes values ranging from 1.1 to 1.3 (with expansion of the FR) and 1.2-1.5 (without expansion). Zuccarello et al (2015) investigated the role of line-tying effects on the eruption. They performed a series of simulations with a setup similar to that of Aulanier et al (2010), but with different velocity drivers at the photosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used value for the critical decay index for the torus instability is 1.5 based on the analytical study by Bateman (1978) and Kliem & Török (2006). However, an extensive MHD simulation study found the critical value lying in the range of 1.3-1.5 (Zuccarello, 2015(Zuccarello, , 2016. Another analytical study found a critical range between 1.1 and 1.3, and it depends on the magnetic field and electric current configuration (Demoulin & Aulanier 2010).…”
Section: Introductionmentioning
confidence: 99%